HUBUNGAN ANTARA AKTIVITAS ANAK PADA PENGGUNAAN METODE KIBAR DENGAN KEMAMPUAN MEMBACA HURUF HIJAIYAH ANAK USIA DINI (Penelitian di Kelompok A RA At-Taqwa Kecamatan Rajapolah Kabupaten Tasikmalaya) - Aulia, Nanda Aulia (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research is based on the problems found, namely that there is a gap between the high activity of children using the kibar method and the low ability to read hijaiyah letters. This can be seen from the enthusiasm of the children when they took part in learning the Koran using the waving method in Group A RA At-Taqwa, Rajapolah District, Tasikmalaya Regency. The purpose of this study was to find out: 1) Children's activity in using the kibar method; 2) The ability to read hijaiyah letters for early childhood; 3) The relationship between children's activities in the use of the waving method and the ability to read hiajiyah letters in early childhood. This study uses a quantitative approach with the correlation method. The subjects in this study were 29 children of group A RA At-Taqwa, Rajapolah District, Tasikmalaya Regency. Data collection techniques used are observation, performance, and interviews. The results of the data analysis showed that the child's activity in the use of the kibar method obtained an average value of 78 in the very good category. Meanwhile, the ability to read hijaiyah letters for early childhood obtained an average value of 66 in the sufficient category. The relationship between children's activities in the use of the waving method and the ability to read hijaiyah letters in early childhood obtained a value of 0.6 in the strong/high category. The contribution given by variable X to variable Y is 36%.